Odpowiedzi

2010-03-07T17:22:57+01:00
A)-17
b)-4
c)-18
d)-49
e)0
F)-7
g)-73
h)-29
1 2 1
2010-03-07T17:25:41+01:00
A) -2-3*5=-2-15=-17
b) (-8):4-2=-2-2=-4
c) 12:(-2)-(-3)=-6-(-3)=-6+3=-3
d) (-2)^3 * 3-25=-8*3-25=-24-25=-49
e) (-15):3 -5*(-1)= -5-5*(-1)=-5+5=0
f) 3*(-7)-7*(-2) = -21+14=-7
g) 6*(-4)+5*(-9) = -24-45=-69
h)(-18):9-(-+27):(-1) = -2-27=29

* - razy
x^y - x do potęgi y
1 5 1
  • Magd
  • Początkujący
2010-03-07T17:29:07+01:00
A)-2-3*5=-2-15=-17
b)(-8):4-2=-2-2=-4
c)12:(-2)-(-3)=-6+3=-3
d)(-2)do3*3-25=-8*3-25=-24-25=-49
e)(-15):3-5*(-1)=-5+5=0
f)3*(-7)-7*(-2)=-21+14=-7
g)6*(-4)+5*(-9)=-24-45=-69
1 5 1